2011
DOI: 10.1248/cpb.59.1157
|View full text |Cite
|
Sign up to set email alerts
|

Pimarane Diterpenes from the Endophytic Fungus <i>Eutypella</i> sp. BCC 13199

Abstract: NoteEndophytic fungi have been proved to be potent sources of novel bioactive compounds. [1][2][3] We recently reported the isolation of two new g-lactones, eutypellins A and B, two enteudesmane sesquiterpenes, ent-4(15)-eudesmen-11-ol-1-one and ent-4(15)-eudesmen-1a,11-diol, and three pimarane diterpenes, diaporthein B (3), 4) scopararane A (4), 5) and libertellenone C (5), 6) from the endophyte Eutypella sp. BCC 13199.7) Since the genus Eutypella has been rarely investigated with only a few other papers des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 11 publications
2
17
0
Order By: Relevance
“…All the above suggested that the carbonyl at position C-7, ∆ 8,14 olefinic bond, whether the C-20 methyl forms a furan ring with C-6, C-5, and C-10, and the number and positions of hydroxyl groups, might be the important structural factors leading to the distinction of their cytotoxicities. Diaporthein B and the 11-dehydroxy derivative of diaporthein B (scopararane A) were reported to show significant cytotoxic activities against human cancer cell lines (KB, MCF-7, NCI-H187) and nonmalignant Vero cells (African green monkey kidney fibroblasts) [10,17], which further demonstrates that the structural features described above are important determinants of cytotoxic activity. The target of the cytotoxic effect of these compounds is still unknown.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the above suggested that the carbonyl at position C-7, ∆ 8,14 olefinic bond, whether the C-20 methyl forms a furan ring with C-6, C-5, and C-10, and the number and positions of hydroxyl groups, might be the important structural factors leading to the distinction of their cytotoxicities. Diaporthein B and the 11-dehydroxy derivative of diaporthein B (scopararane A) were reported to show significant cytotoxic activities against human cancer cell lines (KB, MCF-7, NCI-H187) and nonmalignant Vero cells (African green monkey kidney fibroblasts) [10,17], which further demonstrates that the structural features described above are important determinants of cytotoxic activity. The target of the cytotoxic effect of these compounds is still unknown.…”
Section: Resultsmentioning
confidence: 99%
“…[7]. Although only few chemical investigations of the genus Eutypella were reported, the numerous secondary metabolites from this genus were isolated, including polyketides such as γ-lactones, benzopyran derivatives and cytosporin-related compounds, terpenoids such as ent -eudesmane sesquiterpenes, and pimarane diterpenes, and nitrogenous compounds such as cytochalasin derivatives and cyclic dipeptides [7,8,9,10]. Previously, we have reported eleven terpenoids, five ergosterol derivatives, and two nitrogen-containing metabolites from the culture of E. scoparia FS26 [11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…D-1 was subjected to repeated column chromatography and followed by semi-preparative HPLC separation to give two new pimarane diterpenes, libertellenones M and N (1 and 2) and five known compounds (3 -7). The known compounds were identical to libertellenones A -C (3 -5), [22] eutypellone A (6), [14] and kaempulchraol W (7), [23] respectively (Figure 1).…”
Section: Resultsmentioning
confidence: 83%
“…Eutypella, a less studied genus, was found to be pathogenic causing cankers in grape vines [17–19], maple [20] and also as saprobe of woody angiosperms [21]. Recently, it was also isolated from sea sediment [22] as well as an endophyte from a few pharmaceutically important plants [23, 24]. …”
Section: Discussionmentioning
confidence: 99%